Evaluation of the Effectiveness of Vector Control Programmes in Hospitals Using the CIPP Approach: A Case Study at Dr. Wahidin Sudiro Husodo General Hospital, Mojokerto City - Anjar Pra Setyaningati; Ngadino; Sri Anggraeni; Setiawan; Elys Elisabet (POLTEKKES KEMENKES PONTIANAK, 2025)
Environmental health is a critical factor in preventing vector-borne diseases in hospitals. The Dr. Wahidin Sudiro Husodo General Hospital in Mojokerto City has implemented a vector control programme in accordance with the Ministry of Health of the Republic of Indonesia Regulation No. 2 of 2023. However, monitoring results indicate that the larval index (LI) remains below the standard threshold of ≥95%, while rodent and cockroach densities exceed the established limits. This study aims to evaluate the effectiveness of the vector control programme using the CIPP model (Context, Input, Process, Product). The research method used was qualitative descriptive with SWOT analysis. Data were collected through observations and interviews with sanitation officers in 32 hospital service units. The evaluation results showed that the context, input, and process aspects met the requirements, with each receiving high scores. However, in the product aspect, weaknesses were still found in mosquito and rat population control. Based on the SWOT analysis, the programme is in the aggressive strategy quadrant, which emphasises the utilisation of internal strengths and external opportunities to improve vector control effectiveness. Key recommendations include expanding programme coverage to areas outside the hospital, strengthening the involvement of internal health workers, and modernising the technology-based monitoring system. With the optimisation of these strategies, it is hoped that the vector control programme will be more effective in maintaining environmental health standards in hospitals.